Business Communication by the Riau Coconut Bonsai Community (BKR) in Attracting Business Interest during the Pandemic Among Ornamental Plant Enthusiasts in Pekanbaru - Reza Hermawan; Fharisa Nabila Rizvi; Ronal Kurniawan; Okta Rizal Karsih; Annisa Meliana (Science, Technology, and Education Care, 2026)
Communication plays a vital role in the operation and success of businesses whether multinational, micro, or medium-sized and the communication activities carried out within a business help achieve its objectives. The objective of this study is to determine how the Riau Coconut Bonsai Community uses business communication to attract the interest of ornamental plant enthusiasts in Pekanbaru during the pandemic. This study was conducted from August to December 2021. Observations were carried out at the BKR Secretariat, Jl. Patria Sari No. 57, Rumbai, Pekanbaru. The research was conducted through face-to-face interviews in accordance with health protocol standards. This study employed a descriptive method with a qualitative approach. Data were collected through observation, interviews, and documentation with informants who are members of the BKR community. The results of the study indicate that the business communication employed by the BKR community utilizes the marketing mix strategy (4Ps): place (selection of strategic locations), price (setting affordable and competitive prices), product (providing unique coconut bonsai products with high aesthetic value), and promotion (promotion through social media and exhibition activities). Additionally, interpersonal communication among members and potential customers plays a crucial role in building trust and increasing public interest in joining the business